2021
DOI: 10.3390/agriculture11050449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mechanical and Intelligent Robotic Weed Control Methods on Energy Efficiency and Environment in Organic Sugar Beet Production

Abstract: Rapidly warming climate, tightening environmental requirements, an aging society, rising wages, and demand for organic products are forcing farming to be more efficient and sustainable. The main aim of this study was to perform an analytical analysis and to determine the energy use and GHG emissions of organic sugar beet production using different weed control methods. Seven different methods of non-chemical weed control were compared. Mechanical inter-row loosening, inter-row cutting and mulching with weeds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Mechanical lightweight weeding robots instead of herbicides can also reduce GHG emissions, benefit biodiversity, and prevent herbicide resistance [57]. There are several non-chemical, preventive weed control measures [58] such as a diversified crop rotation, which can reduce the need for herbicides [59], while cover crops and mulching can both suppress weed emergence and promote soil biota [60][61][62]. The environmental impacts of mechanical weed control compared to chemical weed control varies by crop type (mechanical weed control performs best in oilseed rape and maize) and herbicides used, but in every case it is superior in terms of toxic burden to humans and the environment [44,63].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical lightweight weeding robots instead of herbicides can also reduce GHG emissions, benefit biodiversity, and prevent herbicide resistance [57]. There are several non-chemical, preventive weed control measures [58] such as a diversified crop rotation, which can reduce the need for herbicides [59], while cover crops and mulching can both suppress weed emergence and promote soil biota [60][61][62]. The environmental impacts of mechanical weed control compared to chemical weed control varies by crop type (mechanical weed control performs best in oilseed rape and maize) and herbicides used, but in every case it is superior in terms of toxic burden to humans and the environment [44,63].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that manure fertilization is very energy intensive is confirmed by the results of research presented in other sources. Reference [41] states that the highest share of energy consumption in organic beet cultivation was accounted for by manure costs, which varied from 48 to 53%, depending on the weed control method. The results of another study showed that farmyard manure-based energy consumption accounted for the largest share of 45.0-49.3% of total energy input in organic production of winter wheat and spring barley [42].…”
Section: Discussionmentioning
confidence: 99%
“…The systems currently available on the market can be divided into fully autonomous (e.g., Farming Revolution W4 ® , Farmdroid FD20 ® ), and semi-autonomous or tractor mounted (e.g., BoniRob ® , KULTi-Select ® , Ecorobotix ARA ® ) systems (Zhang et al, 2022). The implement guidance of such systems works either via digital image processing algorithms supported by RGB, multispectral or hyperspectral cameras (e.g., Farming Revolution W4 ® , KULTi-Select ® ) or by using an RTK-GNSS signal (e.g., Farmdroid FD20 ® ) (Bručienė et al, 2021). Although development in robotic weeding has made significant progress in recent years, such systems are still difficult to manage.…”
Section: Introductionmentioning
confidence: 99%